Clean Tanks Deliver Quality Water. Issue 12 (1st December 2013) - Cashion, Bob; Peters, Jason
Abstract : Finished water in distribution system storage facilities can undergo changes in water quality. However, with regular storage inspection and cleaning, utilities can preserve water quality and extend tank operating life and their capital budgets.